Rapid invasion of the non-indigenous brown alga Stypopodium schimperi in the Adriatic Sea - LUCIC JELIĆ, PETRA; CVITKOVIĆ, IVAN; NEJAŠMIĆ, JELENA; CVJETAN, SVJETLANA; DESPALATOVIĆ, MARIJA; MUCKO, MAJA; KVESIĆ IVANKOVIĆ, MARIJA; ŽULJEVIĆ, ANTE (Mediterranean Marine Science, 2025)
In this study, we report the first record of the brown alga Stypopodium schimperi in the Adriatic Sea, which also represents the northernmost occurrence of this Lessepsian species within the Mediterranean. Species identification was confirmed through morphological examination and molecular analyses based on genotyping of the chloroplast genes rbcL, psbA, and psaA. During a 3-year observation period, S. schimperi demonstrated a vigorous increase in both coverage and spatial distribution. Starting from a few observed thalli in autumn 2020, coverage reached 100% over a large area. Consequently, this resulted in a drastic reduction of native macroalgae on rocky bottoms, mostly at depths of 5-20 m, which we quantified via photo-quadrat analyses along a gradient of its coverage. In conclusion, this non-indigenous species has the potential to become one of the most invasive in the Adriatic Sea, with a high likelihood of spreading further into the northwestern Mediterranean.